DEVERSITY MANAGEMENT DALAM ORGANISASI/PERUSAHAAN - Maisyura Maisyura; Nanda Ameliany (Program Studi Administrasi Bisnis, 2021)
This paper explores the diversity of human resources/labor in an organization, where every difference in physical, race, gender, language, education meets in a work team that is expected to be able to achieve the vision, mission and goals of the organization/company as well as possible. Management of this diversity is absolutely necessary. Diversity management is expected to be useful in managing diversity within an organization/company. By using a descriptive approach, the author tries to describe how organizations/companies manage the diversity of their human resources, using literacy studies from various sources, both books, articles, and journals related to the theme of this paper. management and implementation of diversity management within the company so as to create harmony and harmony that is able to support the achievement of the vision, mission and goals of the organization as a whole.